Hydrogen combustion in internal combustion engines - Rauker, Josip; Šaban, Andrija (Crisis Management Days, 2024)
Reducing carbon dioxide emissions, as well as other harmful gases generated by the combustion of fossil fuels, is one of today's main priorities. Hydrogen economy is one step in that direction. The basic idea is to replace fossil fuels with hydrogen obtained through environmentally friendly methods. When it comes to motor vehicles, there are two main ways of using hydrogen for propulsion: in fuel cells or by combustion in internal combustion engines. Due to the relatively high cost of fuel cells, some vehicle manufacturers have begun developing hydrogen-powered internal combustion engines. Current research focusing on hydrogen-burning engines shows promising results, although there are still a number of issues that need to be addressed before such engines are ready for the market.